HUBUNGAN PENGETAHUAN, MOTIVASI, DAN PELATIHAN DENGAN KUALITAS PENDOKUMENTASIAN ASUHAN KEPERAWATAN DI RUANG INTERNA RSUD DR. M.M. DUNDA LIMBOTO - Sabirin B. Syukur; Rini Asnawati (program studi ilmu keperawatan fakultas ilmu kesehatan universitas muhammadiyah gorontalo, 2021)
The purpose of this research is to know the relationship of Knowledge, Motivation and Training with Quality Documentation of Nursing Care in Internal Room of RSUD Dr. MM Dunda Limboto. This research use descriptive analytic research design with cross sectional approach. The population of this study is all nurses who are in the internal room of RSUD Dunda Limboto, with a sample size of 35 nurses using Total Sampling technique. Data is collected through Cakeys. The results showed: 1) There is influence of knowledge with documentation quality of nursing care with pvalue value 0.002, 2) There is influence of nurse motivation with documentation quality of nursing care with p value 0,015 3) There is no effect of training with documentation quality of nursing care with pvalue value 0.152.